2001
DOI: 10.1046/j.1365-2567.2001.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of locally produced interleukin‐10 on respiratory syncytial virus infection

Abstract: SUMMARYInterleukin (IL)-10 is known to be a multifunctional cytokine. This study was designed to evaluate the role of IL-10 during respiratory syncytial virus (RSV) infection using a C57BL/6 transgenic (TG) mouse model in which the expression of murine IL-10 cDNA was regulated by a human salivary amylase promoter (IL-10 TG mice). These mice expressed a large amount of IL-10 in the nasal mucosa and in salivary glands. Viral replication in the respiratory tract after intranasal infection with RSV was suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…[35][36][37] Previous studies have examined the consequences of IL-10 depletion in knockout animals and in animals overexpressing IL-10 but not neutralization during infection in a normal animal during primary infection. 38,39 The overexpression of IL-13 in lungs of mice has been clearly linked to pathophysiological changes in not only allergic responses but in several other instances, including RSV infection. 23,40 -42 In the present studies we also demonstrated the relevance of IL-13 in the development of pathophysiology using IL-13 Ϫ/Ϫ mice and indicated a significant attenuation of the developing AHR responses as well as gob5 gene expression during Line 19 RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Previous studies have examined the consequences of IL-10 depletion in knockout animals and in animals overexpressing IL-10 but not neutralization during infection in a normal animal during primary infection. 38,39 The overexpression of IL-13 in lungs of mice has been clearly linked to pathophysiological changes in not only allergic responses but in several other instances, including RSV infection. 23,40 -42 In the present studies we also demonstrated the relevance of IL-13 in the development of pathophysiology using IL-13 Ϫ/Ϫ mice and indicated a significant attenuation of the developing AHR responses as well as gob5 gene expression during Line 19 RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…RSV replication in the respiratory tract is suppressed signiWcantly in IL-10 transgenic mice compared to nontransgenic controls. This suppression can be prevented by administering neutralizing anti-IL-10 antibodies [24]. On the other hand, IL-10 restricts activities of dendritic cells, macrophages, NK cells and T cells, possibly resulting in suppression or anergy of the immune response [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, differential rates and combinations of pro-and anti-inflammatory molecules are likely to influence in a significant manner the outcome of RSV pathogenesis. Furthermore, these findings suggest that the combined secretion of IL-10 in the lungs with Th1-promoting cytokines might reduce to some extent the lung-damage caused by the virus, while the same cytokine in combination with other molecules could contribute to enhancing the pathology [67,72,76,77].…”
Section: Early Immune Response Induced By Rsv Infectionmentioning
confidence: 96%
“…These molecules bind to surface receptors belonging to the type I IFNAR complex, which in turn activate several intracellular signaling pathways that promote the activation of anti-viral responses [83,84]. Such cellular responses are characterized by the expression of interferon-stimulated genes (ISGs) [52,55,72,77,78,81,84,85] that trigger effector functions which include the activation of ribonuclease L for RNA degradation [86], proliferation and activation of NK cells [87]. In the lungs, production of type I IFNs derives mainly from plasmacytoid dendritic cells (pDCs), epithelial cells and macrophages [88,89].…”
Section: Role Of Type I Ifns On Rsv Immunopathogenesismentioning
confidence: 99%